High prevalence of blaCTX-M-1/IncI1/ST3 and blaCMY-2/IncI1/ST2 plasmids in healthy urban dogs in France - Haenni, Marisa; Saras, Estelle; Métayer, Véronique; Médaille, Christine; Madec, Jean-Yves (Antimicrobial agents and chemotherapy, 2014)
In the community, close contacts between humans and dogs may promote the transfer of extended-spectrum beta-lactamase/plasmidic AmpC cephalosporinase (ESBL/pAmpC) genes. Large-scale prevalence studies on ESBL/pAmpC carriage in dogs are rare, and data on ESBL/pAmpC plasmids are even more limited. Here, a considerable rate of 18.5% ESBL/pAmpC carriers was found among 368 unrelated healthy dogs in Paris, France. This prevalence is much higher than the one found in healthy humans in the same city (6%) but close to that recently reported in dogs in China (24.5%). All isolates were identified as Escherichia coli, except one Salmonella enterica and one Klebsiella pneumoniae isolate. The sequence type 131 (ST131) clone was rare (2/73 isolates). Interestingly, two plasmids (blaCTX-M-1/IncI1/ST3 and blaCMY-2/IncI1/ST2) were unexpectedly highly predominant, raising the question of their successful spread. Considering that CTX-M-1 was recently found to be equally as abundant as CTX-M-15 in healthy Parisian subjects, the question of dogs being a CTX-M-1 reservoir for humans is open. Such a high prevalence of the blaCMY-2/IncI1/ST2 plasmid may result from the use of cephalexin in veterinary medicine, as previously demonstrated experimentally. In all, our study points out healthy urban dogs as a potential source of ESBL/pAmpC genes that can further disseminate to the human community.